Growth and Production of Hydroponics Chinese Flat Cabbage With Ab Mix Concentration and Android Based Monitoring - Rusmini Rusmini; Daryono Daryono; Nur Hidayat; Heriad Daud Salusu; Husmul Beze; Yulianto Yulianto (Jurnal Penelitian Pertanian Terapan, 2021)
Hydroponic cultivation is an alternative choice for people who plant various types of plants that can be consumed by themselves every day. In addition, hydroponics is one way to grow crops on a large scale without requiring land that is very suitable for cultivation in urban areas. However, this system has several drawbacks, namely, hydroponics really requires a controlled environment, such as monitoring the degree of water acidity, water temperature, and water nutrient density. It needs to be monitored and controlled to avoid a decrease in plant quality. Several ways can be done by using manual measuring tools which actually take time if the hydroponic system is on a large scale, the alternative is to use an Android-based control and monitoring system. This study aims to examine the effect of the best AB Mix nutrient concentration on the growth and production of Sawi Pagoda with the NFT hydroponic system and to control pH, temperature, humidity and nutrients automatically using the Ardiuno Uno sensor. This research was conducted at Rootop PS. Plantation Cultivation from August to October 2020. The design used was a completely randomized design consisting of one factor, namely the concentration of AB mix nutrients consisting of 2 levels: A1: 1000 ppm: 1200 ppm: 1400 ppm (given according to the age of the plant per / week) and A2: 1100 ppm: 1300 ppm: 1500 ppm (given according to plant age per / week). The research was repeated as many as 20 replications so that there were 40 experimental units. The results showed that the A1 treatment level with the concentration of AB Mix nutrient solution (1000 ppm: 1200 ppm: 1400 ppm) was the best treatment level for the increase in plant height and number of leaves on the 2nd and 3rd week and the final plant weight. The hydroponic Nutrient Film Technique system can be monitored and controlled automatically by Arduino, making it easier to control temperature, humidity, ppm of nutrients, and nutrient pH. Keywords: AB mix, Hydroponics, Mustard Pagoda